INTEGRASI PSIKOLOGI SOSIAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: UPAYA PEMBENTUKAN KARAKTER SISWA DI MA AL-FALAH NAGREG - Ririt Komariah; Shalahudin Ismail; Enden Siti Nur Fathonah; Sahudi Sahudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the importance of applying social psychology in Islamic Education (PAI) learning at Madrasah Aliyah Al-Falah Nagreg, particularly in enhancing students' religious understanding and character development. Social psychology helps teachers understand student interactions and behavior, thereby strengthening the learning process that is not only knowledge-oriented but also focused on character development and social skills. This study employs a qualitative approach using the case study method, conducted at Madrasah Aliyah Al-Falah Nagreg. The study concludes that the application of social psychology in PAI education at Madrasah Aliyah Al-Falah Nagreg effectively improves the quality of education by integrating religious value understanding and character development through social interaction. This approach strengthens cognitive aspects while fostering empathy, responsibility, fairness, and cooperation. Therefore, PAI teachers need to integrate social psychology to create an inclusive learning environment that supports students' character development. The urgency of integrating social psychology into PAI learning lies in its ability to bridge the understanding of Islamic values with the social reality of students. This approach is effective in shaping students' characters to be empathetic, tolerant, and able to practice religious teachings contextually.